The prospective utilization of Luffa fibres as a lignocellulosic bio-material for environmental remediation of aqueous media: A review. Issue 1 (February 2021) - Khadir, Ali; Motamedi, Mahsa; Pakzad, Ebrahim; Sillanpää, Mika; Mahajan, Shreya
Graphical abstract: Highlights: Luffa and its composites have a great potential for efficient elimination of pollutants. The influence of chief operational parameters was explained. Isotherms and kinetic models showed that most investigations followed Langmuir and Pseudo-second order assumptions. The adsorption capacity of Luffa and its composites compared with the others. Abstract: Luffa is an excellent biomaterial that has gained much attention since it is low-cost, available, environmentally-friendly, non-toxic, porous and efficient for the removal of environmental pollutants, including dyes, pharmaceuticals, and heavy metals. This review provides an insight into the key factors, including contact time, pH, pollutant concentration, adsorbent dosage, and temperature that may affect the Luffa performance in removing contaminants. Thereafter, Luffa and its composites were characterized by SEM, FTIR, BET, XRD, EDAX, and TGA. This paper reviews the current state of research on the use of raw Luffa and modified Luffa, and compare the results with other investigations. It was found that Luffa – based composites might be great potential candidates for water decontamination. Adsorption equilibrium and kinetics were also studied and it was found that Langmuir/Freundlich and Pseudo-second order models were in great agreement for many studies. Results confirmed that Luffa and its composites possess good applicability in removing different types of pollutants from aqueous solutions.